Modelling and Validation For Volume Estimation of Eucalyptus - Dugarjav, Delgerjargal; Pandey, Rajiv (Indian Forester, 2009)
Models for volume estimation for Eucalyptus plantation have been developed for NEPA farm, Uttrakhand. The model validation was ranked on the basis of different criteria, namely, adj. R2, bias, variance, root mean square error and coefficient of dispersion. Finally, on the basis of ranking, the models V = - 0.00066 + 0.00003 D2H and V = - 0.05457 + 0.00076 DH were recommended.